2013
DOI: 10.1371/journal.pone.0072608
|View full text |Cite
|
Sign up to set email alerts
|

New Onset of Constipation during Long-Term Physical Inactivity: A Proof-of-Concept Study on the Immobility-Induced Bowel Changes

Abstract: BackgroundThe pathophysiological mechanisms underlining constipation are incompletely understood, but prolonged bed rest is commonly considered a relevant determinant.AimsOur primary aim was to study the effect of long-term physical inactivity on determining a new onset of constipation. Secondary aim were the evaluation of changes in stool frequency, bowel function and symptoms induced by this prolonged physical inactivity.MethodsTen healthy men underwent a 7-day run-in followed by 35-day study of experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 41 publications
3
49
1
2
Order By: Relevance
“…[21,22] Even though those ndings have been described in chronically ill patients, little is known about reduced mobility and the appearance of constipation in a population that previously was apparently healthy, such as the one we evaluated. Our results are similar to those reported by Iovino et al, [15] in a "new-onset" constipation model. Those authors demonstrated that strict bedrest for a period of 35 days, adhered to even to perform daily activities, including defecation, was associated with a high rate of constipation in healthy volunteers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…[21,22] Even though those ndings have been described in chronically ill patients, little is known about reduced mobility and the appearance of constipation in a population that previously was apparently healthy, such as the one we evaluated. Our results are similar to those reported by Iovino et al, [15] in a "new-onset" constipation model. Those authors demonstrated that strict bedrest for a period of 35 days, adhered to even to perform daily activities, including defecation, was associated with a high rate of constipation in healthy volunteers.…”
Section: Discussionsupporting
confidence: 93%
“…[11,13,14] Symptoms of constipation induced by immobility in geriatric patients have been shown to decrease with the regular performance of physical activity. In a unique study on the subject, Iovino et al [15] demonstrated that prolonged physical inactivity (for 35 days, in 10 healthy volunteers) triggered constipation in 60% of the study individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, careful attention to diet and exercise need to be looked after in order to prevent an impaction on the bowel problem from recurring. Moreover, there was a study that indicated FC will arise from physical inactivity, even among healthy individuals [52]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been previously suggested that anorectal dysfunction underlying functional constipation may be an important contributory factor to the development of bloating and abdominal distension [62] . We found that in healthy men who underwent experimentally-controlled 35-d of bed rest, at the end of the study, 60% had new onset of functional constipation fulfilling Rome Ⅲ criteria, moreover, there was a significant increase in flatulence and a significant correlation between the change in flatulence and the change in number of evacuations that significantly decreased [63] . It is possible that during bed rest due to an ineffective evacua- Figure 2 Gas physiology in the gastrointestinal tract.…”
Section: Stoolsmentioning
confidence: 79%